Enhanced crystallinity and thermal stability of Ba2+ and Al3+–O2− co-substituted Sr2Si5N8:Eu2+. Issue 29 (29th June 2020) - Li, Zebin; Seto, Takatoshi; Wang, Yuhua
Abstract : By co-substituting a cation (M 2+ :Ba 2+ or Ca 2+ ) and Al 3+ –O 2− into Sr2 Si5 N8 :Eu 2+ in a solid-state method, we successfully synthesized the nitrido-alumino-silicate phosphors Sr(2− y ) M y Si5− x Al x N8− x O x :Eu 2+ (Ba-AlO-258 (M y = Ba0.3, x > 0) and Ca-AlO-258 (M y = Ca0.3, x > 0)). Abstract : By co-substituting a cation (M 2+ : Ba 2+ or Ca 2+ ) and Al 3+ –O 2− into Sr2 Si5 N8 :Eu 2+ in a solid-state method, we successfully synthesized the nitrido-alumino-silicate phosphors Sr(2− y ) M y Si5− x Al x N8− x O x :Eu 2+ (Ba-AlO-258 (M y = Ba0.3, x > 0) and Ca-AlO-258 (M y = Ca0.3, x > 0)), which were compared with conventional AlO-258 ( y = 0, x > 0), Ba-258 (M y = Ba0.3, x = 0), Ca-258 (M y = Ca0.3, x = 0), and 258 ( y = 0, x = 0). SEM exhibited that the morphology and particle size were very different between Ba-AlO-258 and the Ca-AlO-258 and AlO-258. The crystallinity was evaluated by determining the lattice strain from the peak-width of the XRD pattern. It was found that the crystallinity of Ba-AlO-258 was much higher than that of Ca-AlO-258 and AlO-258 under the same synthesis conditions. We proposed the significance of a size balance between the ionic part, (Ba, Sr, Ca)–(N, O) n, and covalent part, (Si, Al)–(N, O)4 tetrahedron, where the larger Ba 2+ (than Sr 2+ ) matches the larger Al 3+ (than Si 4+ ) in crystal 258. The emission peaks of the three phosphors shifted to longer wavelengths with the substitution of Si 4+ –N 3− with Al 3+ –O 2− . The temperature dependency of our new Ba-AlO-258 was the best in all phosphors. We found that the co-substitution of M 2+ (Ba 2+ or Ca 2+ ) and (AlO) + improved the temperature dependency, although the conventional single substitution of (AlO) + made it worse. From the advanced thermo-luminescence measurement (excitation: blue light), the significant improvement of the temperature dependency of the emission at blue excitation was strongly considered due to a continuous supply of the red emission from the electron at the trap center. The new Ba-AlO-258 is believed to be the best blue LED phosphor in the well-known industrial 258 series because of its superior thermal property and crystallinity.